BODY WEIGHT EFFECT ON JOINT SPACE WIDTH AND TIBIO FEMORAL ANGLE OF KNEE JOINT MEASUREMENT FOR OSTEOARTHRITIS DETECTION USING IMAGEJ - Agung Nugroho Setiawan; Suryono Suryono; Sugiyanto Sugiyanto; Fatimah Fatimah; Gatot Murti Wibowo (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Radiograph of knee joint with Kellgren and Lawrence classification system is the gold standard for assessing knee osteoarthritis. However, these grades are still obstacles. It is sometimes not appropriate to assess the progress of osteoarthritis and very long time to see the results of such progress. Osteoarthritis diagnosis and classification have been relying on qualitative visual interpretation by a radiologist. Probably difficult to determine whether there OA in the knee or not. Image quantification of digital radiography is done by measuring the joint space width and tibio femoral angle of the knee joint using the ImageJ software, with body weight variance as one factor that could affect it. Aims: This research aims to get information of body weight effect on the measurement of the joint space width and tibio femoral angle of knee joint in OA detection. Methods: This is a cross-sectional study. Subjects were digital images of the knee joint anteroposterior (AP) projection using Computed Radiography (CR) from 21 respondents with specific criteria. Image is then quantified using ImageJ software to measure the joint space width and tibio femoral angle. Print out of examination visually evaluated by one radiologist to confirm the diagnosis of OA of the knee joint. Results: The value of the right knee joint space width lateral and medial (3.81 ± 1.18 and 2.42 ± 0.77), while the left lateral and medial (3.49 ± 1.11 and 2.69 ± 0.83). Tibio femoral angle range 168.44 to 178.39 with the average tibiofemoral angle right knee 175.18 ± 2.04 and 173.80 ± 2.44 left knee. Body weight has a significant correlation to the tibiofemoral angle of knee joint (p value < 0,03). Conclusion: The joint space width values that taken from digital quantificationcan be baseline data of respondents, especially for those respondents who had grade 2 or indicated osteoarthritis, to be observed or compared in the next examination.The tibio femoral angle can be addition information in relation with knee pain to detect osteoarthritis.